2002
DOI: 10.1136/adc.86.5.344
|View full text |Cite
|
Sign up to set email alerts
|

Liver disease in transfusion dependent thalassaemia major

Abstract: Aims: To study the prevalence and severity of liver diseases of transfusion dependent thalassaemia major patients, and correlate the histological and biochemical changes of iron overload in liver with the peripheral blood markers. Method: Liver biopsy was performed to assess the histological changes and liver iron content (LIC). Results: One hundred patients were evaluated (median age 11.7 years, range 1.5-27). A total of 81 liver biopsies were performed in 73 patients; 43 samples were analysed for LIC. Grade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 19 publications
2
51
1
2
Order By: Relevance
“…A poor correlation between liver iron stores and serum ferritin level has been shown in patients receiving iron chelator. 34 The correlation is especially poor when serum ferritin exceeds 5500 pmol/L, 35 a level that is exceeded in 30% (9 of 30) of our patients. It remains to be determined whether by using a more robust indicator of tissue iron load, such as liver iron content, 36 a positive correlation between iron load and indexes of vascular function would emerge.…”
Section: Discussionmentioning
confidence: 75%
“…A poor correlation between liver iron stores and serum ferritin level has been shown in patients receiving iron chelator. 34 The correlation is especially poor when serum ferritin exceeds 5500 pmol/L, 35 a level that is exceeded in 30% (9 of 30) of our patients. It remains to be determined whether by using a more robust indicator of tissue iron load, such as liver iron content, 36 a positive correlation between iron load and indexes of vascular function would emerge.…”
Section: Discussionmentioning
confidence: 75%
“…Figure 3 documents the poor association of ferritin and HIC and total body iron previously reported. 2,6 Organ dysfunction due to iron overload was common in young adults with TM (Table 2). Twenty-three percent of patients 25 years or older had heart disease requiring medication.…”
Section: Complications Of ␤-Thalassemia Major 35mentioning
confidence: 99%
“…31 Among 73 TM patients from Hong Kong aged 1.5 to 22.5 years (mean, 11.7 years) and undergoing biopsy from 1992 to 1999, none had evidence of cirrhosis and 30% had liver fibrosis. 6 …”
Section: Iron Overloadmentioning
confidence: 99%
“…2 Multicenter cross-sectional studies have reported that the development and the severity of liver fibrosis are strongly related to the extent of liver iron overload and to the presence of chronic HCV infection. [3][4][5][6][7] Long-term observation of thalassemics who had undergone bone marrow transplantation showed that severe iron overload and chronic HCV infection were independent risk factors for liver fibrosis progression. 8 In the last 20 years, intensive and adequate iron chelation therapy has reduced the iron overload in transfusion-dependent thalassemics, 9 and the screening of blood donors for HCV markers has minimized the risk of de novo HCV infection.…”
Section: Introductionmentioning
confidence: 99%